SAVE THE FOOD FOR A BETTER FUTURE: A DISCUSSION ON FOOD WASTAGE IN MALAYSIA - Nur Fazini Asro Bt. Ramzi Sulaiman; Asmida Ahmad (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
In 2016, the Food Aid Foundation (Food Aid) reported that Malaysian has wasted almost 15,000 tonnes of food including 3000 tonnes of edible food every day. A report shown that Malaysia’s food import bill is said to be between RM35 billion and RM40 billion, which means an average income Malaysian spent about a quarter from their income on food and beverages which later gone to waste. In addition to that the contributors were also including hotels, restaurants, supermarkets and many more production households. Awareness on the food waste or food loss is quite alarming with participation from NGO’s to combat the issue. However, there are no laws on regulation on food waste or food loss management in Malaysia and only a normal standard of procedure is used to dispose the food within 24 hours after its produce. The aim of this article is to discuss possible regulation in addressing the issue. The discussion will also involve comparison of laws and regulations from other countries in handling the same issue. In the end the article seeks to propose a strong guidelines and procedure in managing the food wastage in Malaysia.